Solid-phase diffusion controlled growth of nickel silicide nanowires for supercapacitor electrode - Ramly, Mohammad Mukhlis; Omar, Fatin Saiha; Rohaizad, Aliff; Aspanut, Zarina; Rahman, Saadah Abdul; Goh, Boon Tong (Elsevier, 2018)
This work reports on the influence of nickel (Ni) thickness on the growth of nickel silicide nanowires (NiSi NWs) using a solid-phase diffusion controlled growth treatment. The NiSi NWs were grown on two different substrates (i.e. crystal silicon (c-Si) and Ni foil) which were coated with Ni film with different thicknesses; 110 ± 5 and 220 ± 5 nm. FESEM images revealed that the shape, the size and the density of NiSi on both substrates were strongly dependent on the thickness of Ni film. These NWs exhibited morphology of straight NWs with diameter and length of between 16 to 23 nm and 2.9 to 3.9 µm, respectively. The NWs showed a single-crystalline Ni 3 Si 2 phase with a preferred orientation in the (1 0 0) plane. XRD diffractogram proved that the formation of Ni-rich NiSi NWs is strongly dependent on the Ni film's thickness rather than on the types of substrates. NiSi NF220 demonstrated the highest specific capacity with a maximum value of 313.3 C/g. This is attributed from the high density of NWs which endows more redox reaction and the high conductivity of Ni foil substrate that facilitated the high charge transfer kinetics. The fabricated NiSi NWs//activated carbon-based asymmetric supercapacitor exhibited the maximum energy density of 13.37 W h/kg at 200 W/kg and good cyclic stability with 79% capacity retention after 3000 cycles.